2006
DOI: 10.1111/j.1469-8137.2006.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of the structural genes regulating defense phenylpropanoid metabolism in Populus

Abstract: Summary• Salicin-based phenolic glycosides, hydroxycinnamate derivatives and flavonoidderived condensed tannins comprise up to one-third of Populus leaf dry mass. Genes regulating the abundance and chemical diversity of these substances have not been comprehensively analysed in tree species exhibiting this metabolically demanding level of phenolic metabolism.• Here, shikimate-phenylpropanoid pathway genes thought to give rise to these phenolic products were annotated from the Populus genome, their expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
261
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 272 publications
(272 citation statements)
references
References 91 publications
11
261
0
Order By: Relevance
“…Although clonal variability was less accentuated than variability in metal accumulation capacity, AL35 stood out for its very high PA levels, with a prevalence of conjugated forms, which reached, in the case of Put, a concentration 18-fold higher than that of other clones. The prevalence of conjugated PAs relative to the free forms is consistent with the abundance of phenolic compounds in poplar tissues (Tsai et al 2006). The strong positive correlation across clones between foliar levels of PAs and root Cu concentration (R 2 = 0.79 for total PAs) suggested that Cu rather than Zn drove the longterm PA response.…”
Section: Field Screening Of Tolerant Poplar Clonessupporting
confidence: 51%
“…Although clonal variability was less accentuated than variability in metal accumulation capacity, AL35 stood out for its very high PA levels, with a prevalence of conjugated forms, which reached, in the case of Put, a concentration 18-fold higher than that of other clones. The prevalence of conjugated PAs relative to the free forms is consistent with the abundance of phenolic compounds in poplar tissues (Tsai et al 2006). The strong positive correlation across clones between foliar levels of PAs and root Cu concentration (R 2 = 0.79 for total PAs) suggested that Cu rather than Zn drove the longterm PA response.…”
Section: Field Screening Of Tolerant Poplar Clonessupporting
confidence: 51%
“…A number of core flavonoid enzymes were significantly downregulated, including CHS2, F3H, DFR2, and CHI2 (Table I). In poplar, F3H and CHI are both single-copy genes, while DFR exists as two isoforms; these genes are all wound stress induced and contribute to PA synthesis (Tsai et al, 2006). While we did not detect significant down-regulation of all the isoforms for the flavonoid enzymes using our cutoffs, the analysis confirms that, when overexpressed, MYB182 has repressive effects on the flavonoid pathway.…”
Section: Transcriptome Analysis Of Myb182 Overexpressor Plants Revealsupporting
confidence: 47%
“…A gas chromatography-mass spectrometry (GC-MS) analysis of the metabolomic profiles of expanding floral buds of 16 trees (12 females and 4 males) from two Populus species (Populus deltoides and Populus nigra) was conducted to determine whether secondary metabolites were correlated with gender (Table 2). Species differences in secondary metabolites of Populus are well documented Whatley 1990, 1991a, b;Greenaway et al 1989Greenaway et al , 1992Tsai et al 2006), and male and female flowers of Salix display gender-specific floral scent characteristics (Fussel et al 2007). Our analyses demonstrate metabolite differences between genders, that is, although buds of both species and both genders contain pinobanskin-3-acetate, pinobanksin-3-acetate chalcone and pinobanksin and 3-isobutanoate, the male floral buds contained very low concentrations of these metabolites.…”
Section: Floral Pathogens and Floral Biochemistrymentioning
confidence: 99%